Divergent dynamics between grassland greenness and gross primary productivity across China. (September 2022) - Zhao, Yanni; Peng, Jian; Ding, Zihan; Qiu, Sijing; Liu, Xuebang; Wu, Jiansheng; Meersmans, Jeroen
Highlights: The increase of productivity was higher than greenness across grassland in China. Temperature and precipitation were the main factors influencing grassland change. The sensitivity of productivity to temperature and solar radiation was more than greenness. Precipitation limited the increase of grassland GPP in subtropical and tropical regions. Abstract: Grassland, the most widespread vegetation type in China, has been greening recently.However, the extent to which the greenness has been translated into productivity and the underlying mechanism of the decoupled grassland greenness and productivity remains unclear. In this study, we detected the trend of normalized difference vegetation index (NDVI) and gross primary productivity (GPP) of grassland in China from 2000 to 2019 and analyzed the driving mechanism of the inconsistency between them. It was found that the relative increase rate of productivity (27.27%, p < 0.05) was much greater than that of greenness (14.54%, p < 0.05) across grasslands in China from 2000 to 2019, especially in temperate regions. The temperature and precipitation were the main factors influencing the grassland growth change, and the impact of temperature and shortwave radiation on productivity was greater than on greenness. However, the increase of grassland greenness was not fully translated into productivity in subtropical and tropical grass as well as shrub. This study revealed the dominance of climatic factors in the translation process from ecosystem structure to function, which highlighted the challenge in enhancing carbon uptake capacity of terrestrial ecosystem facing accelerated climate change.